“If I Could but See a Day of it”: On the Aesthetic Potential for Belonging and Action - Goldsmith, Adam J. (Text Matters: A Journal of Literature, Theory and Culture, 2024)
This essay argues that the potential freedom revealed within aesthetic experiences of beauty can encourage a utopian form of belonging that could help materially realize this potential. Drawing upon Immanuel Kant and Friedrich Schiller, while aesthetics offers the occasion to imagine freedom, aesthetics alone cannot make us free. To try to instantiate aesthetic freedom, as Herbert Marcuse notes, is utopian: imagining freedom in an unjust world produces dissatisfaction with reality. Thereby, aesthetic occasions can heighten a longing for the material manifestation of the potential freedom it glimpses. Under the right conditions, such longing encourages be-longing, (and be-longing encourages longing), a deep feeling that can excite wills to act in concert to refashion the world inspired by its image. To demonstrate this, I first read Schiller to display the possibility for aesthetic experiences to offer us back our freedom in potentia. Then, following Marcuse, I explain the utopian character of this aesthetic freedom, as it longs for broader materialization that is not-yet existent. Finally, I sketch how this longing can encourage be-longing through a reading of Kim Stanley Robinson’s novel The Ministry for the Future.